2020
DOI: 10.1021/acsami.0c10587
|View full text |Cite
|
Sign up to set email alerts
|

Two-Dimensional Cs2Pb(SCN)2Br2-Based Photomemory Devices Showing a Photoinduced Recovery Behavior and an Unusual Fully Optically Driven Memory Behavior

Abstract: The rapid development of Internet of Things and big data has made the conventional storage devices face the need of reforming. Rather than using electrical pulses to store data in one of two states, photomemory exploiting optical stimulation to store light information emerges as a revolutionary candidate for the optoelectronic community. However, fully optically driven photomemory with fast data transmission speed and outstanding energy saving capability suffers from less exploration. Herein, a transistortype … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
40
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 45 publications
(43 citation statements)
references
References 57 publications
1
40
0
Order By: Relevance
“…149,150 Through space constraints, perovskite nanocrystals embedded in the polymer matrix may act as charge trapping sites to isolate charges, and the related trapping/untrapping mechanisms can be realized by applying an electric field or using photons. Chueh et al 151 created a transistor memory through Cs 2 Pb(SCN) 2 Br 2 /polymer (SCN -= thiocyanide) hybrid films. The 2D Cs 2 Pb(SCN) 2 Br 2 with intrinsic QW structure exhibited not only considerable photoresponse but also good environmental stability.…”
Section: Novel Memory Devicesmentioning
confidence: 99%
“…149,150 Through space constraints, perovskite nanocrystals embedded in the polymer matrix may act as charge trapping sites to isolate charges, and the related trapping/untrapping mechanisms can be realized by applying an electric field or using photons. Chueh et al 151 created a transistor memory through Cs 2 Pb(SCN) 2 Br 2 /polymer (SCN -= thiocyanide) hybrid films. The 2D Cs 2 Pb(SCN) 2 Br 2 with intrinsic QW structure exhibited not only considerable photoresponse but also good environmental stability.…”
Section: Novel Memory Devicesmentioning
confidence: 99%
“…(C) WRER switching cycle of fully optically driven Cs 2 Pb(SCN) 2 Br 2 /PVP‐based photomemory recorded at V DS = −60 V. Note that the gray shadow, blue shadow, and yellow shadow represent the dark conditions and illumination period of blue laser and white light, respectively. (B),(C) Reproduced with permission: Copyright 2020, American Chemical Society 72 . (D) The schematic device structure of the perovskite flash memory.…”
Section: Organic–inorganic Halide Perovskite Based Neuromorphic Devicesmentioning
confidence: 99%
“…Liao et al reported fully optically driven photomemory based on 2D Cs 2 Pb(SCN) 2 Br 2 72 . Figure 6B shows the device structure of the memory device which consisted of Si/SiO 2 /perovskite‐polymer/pentacene/electrodes.…”
Section: Organic–inorganic Halide Perovskite Based Neuromorphic Devicesmentioning
confidence: 99%
“…Signi cantly, the achieving of su cient dielectric states is still a burden even for noninkjet-printed synaptic transistors, although tremendous contributions have already been made to achieve the nonvolatile behavior based on diverse kinds of dielectric materials (ferroelectric 11,12 , electret [13][14][15] , electrochemical 16,17 , two-dimensional [18][19][20] , hybrid materials [21][22][23] , etc.) and structures ( oating gate [24][25][26][27][28][29][30] , heterojunction 31-34 , etc. ).…”
Section: Introductionmentioning
confidence: 99%